HUBUNGAN ASUPAN ZAT GIZI, AKTIVITAS FISIK, DAN PERSENTASE LEMAK TUBUH DENGAN KEBUGARAN JASMANI (Studi pada Atlet Taekwondo di Hwarang Taekwondo Club Central Semarang) - Rhosidatus Salamah; Apoina Kartini; M. Zen Rahfiluddin (Jurnal Kesehatan Masyarakat (Undip), 2019)
Physical Fitness is the ability of individuals to carry out physical activity easily without experiencing excessive success. To support Atlet's ability to have good physical fitness, intake is needed which has adequate and balanced nutrition. This study aimed to analyze the correlation of nutrient intake, physical activity, and body fat percentage with physical fitness in taekwondo athletes.This type of research is explanatory research with a cross sectional approach. The population was all taekwondo athletes members of the HTC Central Semarang Club (50 subjects). Forty-two subjects were selected by purposive sampling. The sample was chosen by purposive sampling method. Bivariate analysis using correlation Pearson and Rank Spearman test. Multivariate anaIysis using linear Regression Test with Dummy Variable.There were no correlation between level energy consumption (p = 0,528, r= -0,100) and level of fat consumption (p = 0,741 r=0,052) with body fat percentage in taekwondo athletes. There was correlation between level energy consumption (p= 0,035 r= -0,326) and physical fitness in taekwondo athletes. There were no correlation between level of fat consumption (p=0,188) r=-0,207) and physical fitness. There was correlation between physical activity (p = 0,000 r=0,822) and physical fitness. There was correlation between body fat percentage (p = 0,005 r=-0,422) and physical fitness. The results of multivariate analysis showed that physical activity was the variable that was most related to the physical fitness.This study recommended that athletes be able to pay attention to their intake to meet athletes' needs, and improve their physical fitness.